2021
DOI: 10.1007/s43440-021-00236-0
|View full text |Cite
|
Sign up to set email alerts
|

Suramin enhances the urinary excretion of VEGF-A in normoglycemic and streptozotocin-induced diabetic rats

Abstract: Background Vascular endothelial growth factor A (VEGF-A) and P2-receptors (P2Rs) are involved in the pathogenesis of diabetic nephropathy. The processing of VEGF-A by matrix metalloproteinases (MMP) regulates its bioavailability. Since the ATP-induced release of MMP-9 is mediated by P2Rs, we investigated the effect of suramin on VEGF-A excretion in urine and the urinary activity of total MMP and MMP-9. Methods The effect of suramin (10 mg/kg, ip) on VEGF-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In addition, it is likely that suramin may modify the progression of DN by altering VEGF-A binding to receptors. Consistent with this, our previous studies in short-term streptozotocin-induced diabetes showed that suramin affects renal VEGF-A with specific receptors and renal arteries' response to acetylcholine [20,21]. In addition, suramin has been shown to reduce fibrosis and improve renal function, such as reducing proteinuria, in experimental diabetes [22][23][24].…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, it is likely that suramin may modify the progression of DN by altering VEGF-A binding to receptors. Consistent with this, our previous studies in short-term streptozotocin-induced diabetes showed that suramin affects renal VEGF-A with specific receptors and renal arteries' response to acetylcholine [20,21]. In addition, suramin has been shown to reduce fibrosis and improve renal function, such as reducing proteinuria, in experimental diabetes [22][23][24].…”
Section: Introductionsupporting
confidence: 76%
“…With an incomplete understanding of late events in the pathogenesis of DN, we decided to use the long-term streptozotocin-induced diabetes model to investigate the role of VEGF-A in the late stages of the disease. In addition, we used suramin as a pharmacological tool to potentially modify VEGF-A expression or concentration, as we have previously shown that suramin in short-term diabetes increases urinary excretion of VEGF-A without altering its blood concentration [20]. We measured the concentration of VEGF-A in the blood and its excretion in the urine, and both parameters were elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, proper VEGFA level is of great significance for maintaining normal glomerular function. Although some studies have found that there is a higher VEGFA level in diabetes, suggesting that the elevated VEGFA levels are pathogenic markers for diabetes [ 19 ]. However, VEGFA knock out diabetic mice has adverse consequences characterized by global sclerosis and death [ 18 ] which illustrate the opinion that the upregulation of VEGFA in diabetic kidneys may protect the microvasculature from injury and reduction of VEGFA in diabetes may be harmful.…”
Section: Discussionmentioning
confidence: 99%
“…[27] The NLRP3 inflammasome has been linked to the development of various kidney diseases, including acute kidney injury (AKI), chronic kidney diseases (CKD), and DN. [28] Anti-vascular endothelial growth factor (VEGF) antibodies reduce hyperosmolarity and proteinuria in diabetic rats, [29] and VEGF is an important component of DN angiogenesis. [28,30] Consequently, we chose three exemplary genes from the aforementioned list of 37 prospective therapeutic target genes for DN to determine their usefulness in the treatment of DN.…”
Section: Tskpd Inhibits Renal Fibrosis In the Dn Mouse Modelmentioning
confidence: 99%